Investigating Effect of Rapamycin and Metformin on Angiogenesis in Hepatocellular Carcinoma Cell Line - Mandana Rastegar; Haji-Amin Marjani; Yaghoub Yazdani; Majid Shahbazi; Masoud Golalipour; Touraj Farazmandfar (Tabriz University of Medical Sciences, 2018)
Purpose: Human hepatocellular carcinoma is one of the most common causes of death in the world. Metformin and rapamycin may decrease the expression of VEGF protein and subsequently angiogenesis. The purpose of this study was to evaluate the effect of these two drugs on expression of VEGF protein and the cell proliferation in the hepatocellular carcinoma cell line (ATCC HB-8065). Methods: HepG2 was cultured in RPMI-1640 medium at 37°C for 48h as a pre-culture and then treated by different concentrations of metformin (0, 5, 10 and 20 mM) and rapamycin (0, 5, 10 and 20 nM) at different times (12, 24 and 48 h). Cell viability was assessed by the MTT assay. Total RNA was extracted by the Trizol reagent and VEGF gene expression was analyzed by quantitative real-time PCR and was calculated by 2-ΔCt method. The VEGF protein level was determined by Elisa assay. Finally, Apoptosis index was calculated by DAPI staining. Results: Metformin and rapamycin significantly decrease cancer cells viability (p<0.05). Rapamycin but not metformin decreases VEGF gene expression in HepG2 cells. Metformin and rapamycin significantly induce cell apoptosis in hepatocellular carcinoma (HCC) cells. Conclusion: Metformin and rapamycin have an anti-tumor effect on HCC. According to our data rapamycin might have an anti-angiogenesis effect via inhibition of VEGF expression. Our results provide an insight into future clinical strategies to improve chemotherapy outcomes in HCC.